Evaluating the roles of detailed endocardial structures on right ventricular haemodynamics by means of CFD simulations. (9th August 2018) - Sacco, Federica; Paun, Bruno; Lehmkuhl, Oriol; Iles, Tinen L.; Iaizzo, Paul A.; Houzeaux, Guillaume; Vázquez, Mariano; Butakoff, Constantine; Aguado‐Sierra, Jazmin
Abstract: Computational modelling plays an important role in right ventricular (RV) haemodynamic analysis. However, current approaches use smoothed ventricular anatomies. The aim of this study is to characterise RV haemodynamics including detailed endocardial structures like trabeculae, moderator band, and papillary muscles. Four paired detailed and smoothed RV endocardium models (2 male and 2 female) were reconstructed from ex vivo human hearts high‐resolution magnetic resonance images. Detailed models include structures with ≥1 mm 2 cross‐sectional area. Haemodynamic characterisation was done by computational fluid dynamics simulations with steady and transient inflows, using high‐performance computing. The differences between the flows in smoothed and detailed models were assessed using Q‐criterion for vorticity quantification, the pressure drop between inlet and outlet, and the wall shear stress. Results demonstrated that detailed endocardial structures increase the degree of intra‐ventricular pressure drop, decrease the wall shear stress, and disrupt the dominant vortex creating secondary small vortices. Increasingly turbulent blood flow was observed in the detailed RVs. Female RVs were less trabeculated and presented lower pressure drops than the males. In conclusion, neglecting endocardial structures in RV haemodynamic models may lead to inaccurate conclusions about the pressures, stresses, and blood flow behaviour in the cavity. Abstract : The effect of detailed endocardial structures on RV haemodynamics was investigated using CFD simulations; trabeculae down to 1 mm 2 cross‐sectional area were segmented from human perfused hearts. Smoothed vs detailed models showed that ventricular trabeculations and papillary muscles increase the intra‐ventricular pressure drop, decrease the wall shear stress, cause turbulent flow and generate secondary vortices, absent in smoothed geometry simulations. The highest correlation to the pressure drop magnitude was the angle at which the inlet and outlet valves are located.